(untitled) (Namibia Educational Reform Forum Journal, 2020)
This study aimed to adapt and validate a questionnaire for assessing Namibian senior secondary (Grades 11 and 12) students’ scientific epistemic beliefs (SEB) and explore their relation to achievement in science, gender, grade and socioeconomic status using paper and pencil. The study was correlational, with a sample of 944 (45% male; 55% female) Grades 11 and 12 students with the mean age M=17.9, SD= 1.4. The study adapted the scientific epistemic beliefs questionnaire developed by Conley, Pintrich, Vekiri and Harrison (2004). The adaptation entailed shortening the questionnaire to mitigate redundancy suspected in the original questionnaire. The self-reporting Likert scale questionnaire comprised of four dimensions of beliefs: source; certainty; development; and justification of scientific knowledge. The adapted questionnaire had good reliability with the Cronbach’s alpha of subscales ranging from .80 to .83 and the overall reliability of .70. Model fit analysis yielded good statistical fit with Chi-square ratio to degrees of freedom= 2.71, RMSEA= 0.043, CFI= 0.95, TLI= 0.94, SRMR= .032. The overall regression model was significant F (4, 939) =8.218, p <.001, R2= .034. Two dimensions, certainty (=.154, p<.001) and justification (=.100, p<.05) were statistically significantly predicted achievement in science. There was statistically significant difference in beliefs about source in terms of gender and grade and about certainty in terms of grade. The results show that the questionnaire works well with the Namibian sample used given the good model fit for the data and reliability. Results are further discussed in terms of 21st century skills development.